TANAMAN HERBAL SEBAGAI TANAMAN HIAS DAN TANAMAN OBAT - Fajar Hidayanto (UII, 2015)
Herbal plant is plant that have been identified and are known by humanobservation has useful compounds to prevent, cure, perform specific biologicalfunctions, to prevent the attack of insects and fungi. With so many benefits that can beobtained from herbs, utilizing the yard area as the land to grow the herbs will bringmany benefits. Herbal plants that do not require large areas for planting will greatlyfacilitate cultivation. In conjunction with Tilik event at 2016, the author initiated asocialization and direct practice home gardens as growing media herbs. With hope, willprovide many benefits for the citizens of Dukuh Jati, Desa Gerposari, Kulon Progo,Yogyakarta.